Challenges and Opportunities In Government Procurement Law In The Digital Era - Kelvin Hartanto Winata; Christina Samangun (Green Publisher Indonesia, 2024)
Procurement of government goods and services is one of the important activities that must be carried out by the government to meet its needs in carrying out its duties and functions. Government procurement of goods and services also plays a role in spurring economic growth and improving community welfare. The aim of this research is to analyze the legal challenges and opportunities for government procurement of goods and services in the digital era. This research uses normative juridical research methods. The data collection technique used in this research is literature study. The data analysis technique used in this research is qualitative analysis. The research results show that the digital era has brought changes and new challenges in the procurement of government goods and services, including cyber security, unclear regulations and competitive inequality. Meanwhile, legal opportunities for government procurement of goods and services in the digital era include efficiency and effectiveness, transparency and accountability, and increased participation.